2020
DOI: 10.1097/pcc.0000000000002427
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After In-Hospital Pediatric Recurrent Cardiac Arrests*

Abstract: Objectives: The objective of this study is to determine outcomes of recurrent cardiac arrest events in the general pediatric inpatient population. Design: Retrospective cohort study of inpatients in a single institution. Setting: A tertiary care free-standing children’s hospital. Patients: All patients less than 18 years old at Seattle Children’s Hospital with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…Several previous investigations (5–7) have reported that AACD-CPR significantly improves the rates of ROSC and 24-h survival in patients who experienced in-hospital CA, with or without chest trauma. However, in our study, although lactic acidosis in the AACD-CPR group, which is associated with poor prognosis (32,33), was much milder compared with the STD-CPR group, this experiment did not demonstrate any increase in ROSC or survival rates at 4, 24, 48, and 72 h in the AACD-CPR group, which differs from previous reports (5–7). These inconsistencies may be attributed to the use of different resuscitation device and trial models.…”
Section: Discussioncontrasting
confidence: 99%
“…Several previous investigations (5–7) have reported that AACD-CPR significantly improves the rates of ROSC and 24-h survival in patients who experienced in-hospital CA, with or without chest trauma. However, in our study, although lactic acidosis in the AACD-CPR group, which is associated with poor prognosis (32,33), was much milder compared with the STD-CPR group, this experiment did not demonstrate any increase in ROSC or survival rates at 4, 24, 48, and 72 h in the AACD-CPR group, which differs from previous reports (5–7). These inconsistencies may be attributed to the use of different resuscitation device and trial models.…”
Section: Discussioncontrasting
confidence: 99%
“…15,16 In our previous study, we found that metabolic acidosis and MODS in the peri-arrest period were associated with mortality in patients with RA. 17 In a recent singlecenter study of adult patients experiencing IHCA, lactic acidosis and RA were shown to be associated with increased mortality. 18 Severe acidosis and MODS in the peri-arrest period may reflect an acute state of inadequate oxygen delivery which is potentially reversible in which case, early initiation of ECLS may help to prevent early RA.…”
Section: Discussionmentioning
confidence: 99%